IMPLEMENTASI FATWA DSN MUI NOMOR:92/DSN MUI/IV/2014 TENTANG PEMBIAYAAN YANG DISERTAI RAHN PADA PRODUK ARRUM HAJI PEGADAIAN SYARIAH JENEPONTO - Nurul Hikmah AS; Hasanna Lawang; M Akil; Andi Bunyamin; Syarifa Raehana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the implementation of the Fatwa of the National Sharia Council of the Indonesian Ulema Council Number 92/DSN-MUI/IV/2014 concerning financing accompanied by rahn for the Arrum Haji product at Pegadaian Syariah Jeneponto. The focus of this study is to analyze the operational system of the Arrum Haji product and its compliance with the fatwa provisions. This study aims to determine the operational mechanism of Arrum Haji financing and assess its level of sharia compliance. Theoretically, this study is expected to enrich the study of sharia economic law, while practically it can serve as evaluation material for Pegadaian Syariah and a source of information for the public. This study uses a qualitative method with a case study approach. Data were collected through observation, interviews, documentation, and literature review. Data analysis was carried out through the stages of data reduction, data presentation, verification, drawing conclusions, and triangulation to ensure data validity. The results show that the Arrum Haji operational system is implemented systematically through the stages of financing application, eligibility verification, submission of collateral in the form of gold or diamonds, signing the contract, and opening a hajj savings account at a partner sharia bank. Next, Pegadaian transfers the initial Hajj deposit funds so that customers can obtain a portion number from the Ministry of Religious Affairs. In terms of fatwa implementation, the Arrum Haji product complies with Sharia principles through the use of qardh, rahn, ijarah, and kafalah contracts. Pegadaian's revenue comes from collateral maintenance fees (mu'nah) and agreed-upon administration fees, thus avoiding any element of usury (riba).